Effectiveness of a smartphone app to increase parents' knowledge and empowerment in the MMR vaccination decision: A randomized controlled trial - Marta Fadda; Elisa Galimberti; Maddalena Fiordelli; Luisa Romanò; Alessandro Zanetti; Peter J. Schulz (Taylor & Francis Group, 2017)
Researchers are trying to build evidence for mhealth effectiveness in various fields. However, no evidence yet is showing the effectiveness of mhealth on parents' attitudes and behavior with regard to recommended vaccination of their children. The aim of this study was to look into the effects of 2 smartphone-based interventions targeting MMR vaccination knowledge and psychological empowerment respectively. The interventions used gamification features and videos in combination with text messages. We conducted a 2x2 between-subject factorial randomized controlled trial (absence/presence of knowledge intervention X absence/presence of empowerment intervention) with parents of young children in Italy. We randomly allocated 201 eligible participants to one of the 4 conditions. Data were collected by questionnaires at baseline and posttest. Primary outcomes were MMR vaccination knowledge, psychological empowerment, risk perception, and preferred decisional role; secondary outcomes included MMR vaccination intention, attitude, confidence, and recommendation intention. A significant gain in vaccination knowledge was reported by all experimental groups compared with the control (F(3,179) = 48.58, p < .000), while only those receiving both interventions reported a significant increase in their psychological empowerment (t(179) = −2.79, p = .006). Participants receiving the intervention targeting knowledge reported significantly higher intention to vaccinate (t(179) = 2.111; p = .03) and higher confidence in the decision (t(179) = 2.76; p = .006) compared with the control group. Parent-centered, gamified mobile interventions aimed at providing parents with vaccination-related information can be used to increase their knowledge, their intention to vaccinate as well as their confidence in the vaccination decision.